Career Adaptability Karyawan dalam Career Statification Pada Badan Pembinaan Ideologi Pancasila - Anjelina , Septina Fitri; Nazriah, Ainun (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
The Badan Pembinaan Ideologi Pancasila (BPIP) still employs contract employees with a ratio of 70:30 between ASN (Civil Servants) and contract employees, where ASN are more dominant. This poses a challenge for contract employees as the dominance of ASN reduces their chances of being appointed as permanent civil servants (PNS). Additionally, contract employees at BPIP Jakarta face heavy workloads, often including working on weekends. This study aims to analyze the adaptability of contract employees at BPIP Jakarta and to find solutions to the problems they face. It also identifies the factors that support and hinder the adaptability of contract employees. The results show that the adaptability of contract employees at BPIP Jakarta is quite good due to career development training provided by BPIP. However, work relationships are less satisfactory due to seniority and status differences between ASN and contract employees. The main problem is that some contract employees are unable to perform their duties because they are not in line with their educational background. To address this, BPIP provides job orientation and specialized training. Factors affecting the adaptability of contract employees include limitations in skills and knowledge for career development, as well as difficulties in creating harmonious work relationships due to status disparities.